The Property of Semi-Kelley for Hausdorff Continua - Chacón-Tirado, Mauricio; de J. López, María (Topology Proceedings, 2021)
In this paper we introduce the property of semi-Kelley for Hausdorff continua. We use this notion to characterize Hausdorff continua with the property of Kelley. We prove that if a product of Hausdorff continua has the property of semi-Kelley, then each factor continuum has the property of Kelley. Concerning hyperspaces, we prove that if either C(X), C_n(X), or 2^X has the property of semi-Kelley, then X has the property of Kelley.